Identifikasi Penalaran Kreatif-Imitatif Siswa dengan Gaya Kognitif Reflektif - Durrotun Nabilah; Ismail; Elly Matul Imah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is aimed to describe the creative and imitative reasoning of students with reflective cognitive styles on math problem solving. The study uses a qualitative approach with a data collection instrument used of Matching Familiar Figure Tests, math ability test, mathematical problem-solving tasks, and interview guidelines. The research result studies indicate that a student with reflective cognitive style that have imitative reasoning in problem solving is less able to provide comprehensive information, still using a problem-solving strategy previously known, nor does he make a return check on the results received. It is different with reflective subjects that have proven creative reasoning capable of delivering well-known information, that can provide novel and thought-provoking solutions. Moreover, he also looking back the resulting solutions to the problem.